2006
DOI: 10.1007/s10612-006-9017-x
|View full text |Cite
|
Sign up to set email alerts
|

‘I Wasn’t Really Bonded with My Family’: Attachment, Loss and Violence among Adolescent Female Offenders

Abstract: This study analyzes the role of trauma and disrupted attachments in the development of adolescent girls' violent behavior. A grounded theory approach was applied to the narratives of 24 young women (age 13-16 years old) who were adjudicated and remanded to custody for an assault or robbery. Three types of loss were inductively derived from the data (death of a loved one, physical absence, and psychological unavailability) as were two categories of violence (in the home and in the community). Findings suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(11 citation statements)
references
References 28 publications
(21 reference statements)
0
9
1
1
Order By: Relevance
“…Aside from the research usefulness of ACASI, because studies have suggested that participants may report more honestly with ACASI (Hewett et al, 2003;Renker & Tonkin, 2007;Turner et al, 1996), it could be quite useful clinically, especially in detention settings where risk profiles are typically high. The rate of reported physical abuse (25.7%) and sexual abuse (11.4%) in our study is outside the range of estimates for physical abuse (57-81%) (Acoca & Dedel, 1998;Belknap & Holsinger, 2006;Chamberlain & Moore, 2002;Ryder, 2007;Simkins et al, 2004) and sexual abuse (25-67%) (Abrantes, Hoffman, & Anton, 2005;Acoca & Dedel, 1998;Alemagno et al, 2006;Belknap & Holsinger, 2006;Chamberlain & Moore, 2002;Dembo, Williams, & Schmeidler, 1993;Goodkind, Ruffolo, Bybee, & Sarri, 2009;Gover, 2004;Lederman et al, 2004;Ruffolo, Sarri, & Goodkind, 2004;Simkins et al, 2004) reported by justiceinvolved girls. The ACASI technology may have contributed to these lower rates.…”
Section: Refusalscontrasting
confidence: 67%
“…Aside from the research usefulness of ACASI, because studies have suggested that participants may report more honestly with ACASI (Hewett et al, 2003;Renker & Tonkin, 2007;Turner et al, 1996), it could be quite useful clinically, especially in detention settings where risk profiles are typically high. The rate of reported physical abuse (25.7%) and sexual abuse (11.4%) in our study is outside the range of estimates for physical abuse (57-81%) (Acoca & Dedel, 1998;Belknap & Holsinger, 2006;Chamberlain & Moore, 2002;Ryder, 2007;Simkins et al, 2004) and sexual abuse (25-67%) (Abrantes, Hoffman, & Anton, 2005;Acoca & Dedel, 1998;Alemagno et al, 2006;Belknap & Holsinger, 2006;Chamberlain & Moore, 2002;Dembo, Williams, & Schmeidler, 1993;Goodkind, Ruffolo, Bybee, & Sarri, 2009;Gover, 2004;Lederman et al, 2004;Ruffolo, Sarri, & Goodkind, 2004;Simkins et al, 2004) reported by justiceinvolved girls. The ACASI technology may have contributed to these lower rates.…”
Section: Refusalscontrasting
confidence: 67%
“…The language of these research participants is the language of disrupted attachment and object relations (Klein, 1946;Ryder, 2007). Each case extract resonates with psychosocial themes and illustrates arguably unsuccessful attempts to address and manage troubled inner worlds.…”
Section: Discussionmentioning
confidence: 91%
“…When children grow up in social environments that enable sensitive and responsive interactions with caregivers, the resultant strong emotional ties facilitate healthy adjustments over the life course: this becomes an internal model that aff ects all future relationships (Collins and Sroufe 1999). When those early attachments are disrupted or malformed, however, whether by abuse, violence, loss or neglect, children are likely to experience social detachment more generally (Hayslett-McCall and Bernard 2002 ;Ryder 2007 ). Eff orts to create or re-create attachments to others, while simultaneously attempting to counteract traumagenic eff ects such as overwhelming feelings of anxiety, rage and shame, are often the very behaviours that bring girls to the attention of the justice authorities.…”
Section: A Change In Course: Youth Relationships and Community-basedmentioning
confidence: 99%